The impact of scarcity and abundance in food chains on species population dynamics - Thomas Eichner; Rüdiger Pethig (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2003)
The population dynamics in a food chains are derived from a sequence of short- run equilibria of an ecosystem where predator species demand prey biomass, supply own biomass to their predators and are assumed to behave as if they maximize net biomass intake. Introducing prices as scarcity indicators for the biomass of each species enables us to determine a short-run ecosystem equilibrium guided by prices. Equilibrium regimes differ with respect to their mix of zero-priced (= abundant) and positive-priced (= scarce) species. The population dynamics turn out to vary with the prevailing equilibrium regime. Our analysis yields a richer and more complex population dynamics than the traditional predator-prey dynamics of the Lotka-Volterra type.
Keywords: 330; Bioökonomik; Intertemporales Gleichgewicht; Marktmechanismus; Theorie